Establishing volumetric biomarkers in MRI of the digestive tract - Pritchard, Susan Elizabeth (2015)
This extended abstract describes the background to the 14 research papers that the author, as staff candidate, is submitting for the award of PhD by published works. The core part of this work refers to the development of volumetric biomarkers within the human digestive tract using magnetic resonance imaging (MRI) and their application to answer novel biomedical research questions. In particular the author’s work has focussed on applying these techniques within the human colon and the first two papers (which detail this work) were led and written by the author. This work was pioneering in its field, the first time that physiologically undisturbed colon volumes were measured in healthy human subjects and in patients suffering from irritable bowel syndrome (IBS) and provided novel insights into the post-prandial symptoms experienced. Subsequently the effect of an experimental stress on this post prandial response was evaluated in healthy subjects, also the first time such an effect had been measured. The third paper, also written by the author, describes her work on the first clinical application of similar volumetric techniques to assess the human nasal airways and their response to pharmacological intervention, in this case the efficacy of a nasal decongestant.